Strategic Sampling of Eurasian Otter Spraints for Genetic Research in South Korea: Enhancing PCR Success and Data Accuracy - Jee Hyun Kim; Jangmi Lee; Dong Youn Kim; Yoon-Do Yang; Sujoo Cho; Han-Chan Park; Sung Yong Han; Mi-Sook Min; Hang Lee; Je-Yoel Cho; Puneet Pandey (Animals)
Non-invasive genetic approaches, particularly using fecal samples, are commonly used to study endangered and elusive species, as they are easy to collect with minimal permission and cause little disturbance to the subject population. However, such studies face limitations due to poor DNA yield, which affects the overall utilization of collected samples and increases data errors. Here, we evaluated the impact of sample age and collection season on the performance of DNA extracted from feces (spraints) of the Eurasian otter (Lutra lutra), a semi-aquatic apex predator in South Korean freshwater ecosystems. We found that PCR amplification success rates decreased more rapidly in summer (79.3–58.2%) compared to winter (99.2–84.8%) with extended environmental exposure. Genotyping error rates were higher in samples collected during summer, with the rate of error increase over time being significantly greater in summer than in winter. The hot and humid South Korean summer fosters microbial growth and fecal degradation, which negatively impacts DNA yield, reducing PCR amplification success and increasing genotyping errors. We recommend collecting otter feces during winter for better DNA quality. If sampling in summer is unavoidable, it is crucial to collect fresh samples, which can be facilitated by conducting frequent surveys of latrine sites.